The Comparative Evaluation of Hospitalized Elderly Patients with COVID-19 from the Onset of the Disease to Recovery and Death in Iran - Barat Barati; Masoumeh Kaydani; Fatemeh Ahmadpour; Mojtaba Kalantar; Fariba Farhadi Birgani (Fasa University of Medical Sciences, 2023)
Background & Objectives: Numerous studies have shown that the risk of death is higher in elderly patients with COVID-19. In Iran, due to the growth of the elderly population and the prevalence of underlying diseases, it is necessary to pay attention to this age group of patients. In this study, clinical, radiological, PCR, and laboratory data of elderly patients with COVID-19 were collected and analyzed in two groups of recovered and dead patients. Materials & Methods: This is a retrospective study of 196 consecutive elderly patients with COVID-19 hospitalized from March 21, 2020, to April 3, 2020, and their follow-up until April 23, 2021. Clinical characteristics, laboratory results, PCR, chest CT scans and Hounsfield Unit data were collected and analyzed in two groups of recovered and dead patients. Obtained Data were analyzed using SPSSv22.0 and MATLAB-R2017 software. Results: The results showed that there were no specific symptoms to distinguish the death group from the recovery group. Significant differences were observed between the two groups for red blood cell counts, hemoglobin, MCHC and MCV levels, bilirubin, aminotransferase levels, CRP, white blood cells, serum BNU, creatinine and PT coagulation index. The concentrations of VBG (HCO3) and VBG (PCO2) in the deceased patients suggest compensated respiratory alkalosis. CT sensitivity is 100% for patients in advanced and severe stages of the disease. Conclusion: The patients in the death group had more underlying diseases than the recovered group. COVID-19 patients are more likely to die when they have both diabetes and cardiovascular disease.